IMPROVING EARLY CHILDHOOD TEACHERS SKILLS IN CREATING ANIMATED ENGLISH LEARNING MEDIA THROUGH POWERPOINT-BASED ANIMATED MEDIA TRAINING - Eva Silvania; Enceng Mulyana; Sri Nurhayati (IKIP Siliwangi Bandung, 2024)
The issue addressed in this study is early childhood teachers' limited ability to create animated English learning media. Training is one strategy for enhancing teachers' competence. Among the abilities is the ability to create animated educational media. The purpose of this study is to determine the effect of animated learning media created with Powerpoint on the ability of early childhood teachers to create animated English learning media. The descriptive qualitative method is used in this study. The respondents in this study included 29 respondents who participated in the introductory research stage and 14 respondents who participated in the training stage. The results indicate that training is being conducted to improve early childhood teachers' abilities to create animated learning media using Powerpoint. As a result, they can incorporate these learning media into their English instruction.